Study of Pumpkin Drying Through Magnetic Resonance Imaging - Ripoli, Cristina; Adiletta, Giuseppina; Russo, Paola; Funicello, Nicola; Iannone, Gerardo; Di Matteo, Marisa; De Pasquale, Salvatore (Frontiers in Sustainable Food Systems, 2021)
Nuclear Magnetic Resonance (NMR) and Magnetic Resonance Imaging (MRI) techniques are widely used in food science, mainly because they are non-invasive techniques. MRI, as a non-destructive technique, allows the study of intact samples and without any preparation of the samples before analysis. In food processing, the monitoring of distribution and water content is a consolidated analysis technique, frequently used on the market in order to preserve appropriate nutritional and health characteristics of food according to quality standards. In a food matrix, the variation of the water content is related to the changes in the internal structure and in the physico-chemical properties that occur during the transformation process. In this study MRI technique is used to evaluate the variation of the water content as a function of the drying time. Pumpkin samples are analyzed at four different drying temperatures of 50, 60, 65, and 70°C. The transverse relaxation time, T2, is used to assess the hydration level of the samples by comparing the information extracted from MR images with the drying kinetics measured by gravimetric method. Moreover, T2 maps are used to correlate the change in water distribution with the change in T2 values. The results show that the global weight loss curves obtained with the standard gravimetric method and with the MRI data are in excellent agreement. This work indicates that monitoring changes in the T2 profile of food (i.e., pumpkin) is a useful method for evaluating moisture profiles and changes induced on the sample during the drying process.